Contratação de bens, serviços e obras na universidade federal de campina grande e sustentabilidade ambiental - Souza, José Roberto de (2017)
Climate change in the last decades is increasingly devastating, and scientific evidence warns that it comes from the environmental degradation imposed by society today on the planet's ecosystems, whose capacity for supply is no longer able to meet the production of goods and services necessary for the well-being of everyone. The responsibility for balancing the demand and consumption of natural resources must be shared between public authorities, business and society in general. In this context, the objective of this study is to analyze the budget and the ways of contracting for goods, services and work at the Federal University of Campina Grande in order to verify to what extent they meet the environmental sustainability criteria established by current legislation, covering the period from 2011 through 2015. The research seeks to address the theme of sustainable development, environmental sustainability and sustainable contracts. This is a case study with an inductive method of approach. As to the objectives, the research is applied, exploratory and descriptive. It is also bibliographical and documentary, as well as quantitative and qualitative. Information about the budget was retrieved from the Public Transparency Portal and the Management Reports, available on the Institution's website. Data related to the contracting for sustainable and non-sustainable goods, services and work were collected in the Federal Government Purchasing Portal, all of which were analyzed and interpreted according to the research objectives. The civil servants’ perception regarding sustainable contracting was investigated with the application of two questionnaires, the first one being applied in the Administrative Rectorate, where the hiring is formalized, and the second was answered by the administrative coordinators of the Academic Units, who were applicants for these goods and services. The collected data were described and interpreted by means of descriptive statistics techniques and correlation analysis to facilitate the understanding of the results presented. The analysis of the data shows that the number of sustainable contracts in the overall total of contracts is inexpressive, and that the civil servants still give little importance to the sustainable contracts as instruments of public management and preservation of the environment. The motivation for embark on this study is to deepen the reflections on the subject of public contracts, in favor of the country’s sustainable development, in its economic, social and environmental aspects.